A Novel Family of Escherichia coli Toxin-Antitoxin Gene Pairs - Brown, Jason M. (American Society for Microbiology, 2003)
Bacterial toxin-antitoxin protein pairs (TA pairs) encode a toxin protein, which poisons cells by binding and inhibiting an essential enzyme, and an antitoxin protein, which binds the toxin and restores viability. We took an approach that did not rely on sequence homology to search for unidentified TA pairs in the genome of Escherichia coli K-12. Of 32 candidate genes tested, ectopic expression of 6 caused growth inhibition. In this report, we focus on the initial characterization of yeeV, ykfI, and ypjF, a novel family of toxin proteins. Coexpression of the gene upstream of each toxin restored the growth rate to that of the uninduced strain. Unexpectedly, we could not detect in vivo protein-protein interactions between the new toxin and antitoxin pairs. Instead, the antitoxins appeared to function by causing a large reduction in the level of cellular toxin protein.